Natural History of a Giant Coronary Aneurysm With Spontaneous Dissection - Bouzas‐Mosquera, Alberto (Clin Cardiol, 2009)
Primary spontaneous coronary artery dissection may appear in young women during the peripartum period or as a result of atherosclerosis. We present a patient with familial hypercholesterolemia who developed a giant aneurysm of the right coronary artery in the setting of atherosclerotic spontaneous coronary dissection over an 8 year period. This report illustrates the association between spontaneous coronary artery dissection and subsequent coronary aneurysm formation. Copyright © 2009 Wiley Periodicals, Inc.